IMPROVING THE ACCOUNTING OF EXPENSES ON DEBT OBLIGATIONS IN ECONOMIC ENTITIES - Kozimjonov , Abrorbek (Innovative Development in Educational Activities, 2023)
This article discusses the problem of financial leasing accounting by business entities in accordance with International Financial Reporting Standards and the capitalization of interest expense on financial lease and their solutions.